Analysis of Influence of Motivation, Competence, Compensation toward Performance of Employee - Tati Hartati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Motivation, competence, compensation and performance are important factors in an organization to achieve its stated goals. This study will examine empirically related to motivation, competence and compensation for its effect on employee performance. The research method used in this research is quantitative with survey techniques. The sample in this study were employees. Determination of the sample is done by proportional random sampling. Sources of data in this study are primary and secondary data. The analysis technique used in this study is path analysis. The results of the study prove that motivation, competence, compensation and performance are in the category of being headed well. While the results of verification studies prove that motivation, competence and compensation have a significant effect both partially and simultaneously on employee performance.